The Chinese National Spirit : The Core of a Spiritual Home - Ouyang, Kang (Springer Singapore : Imprint: Springer, 2017)
<characteristics. this="" model="" can="" be="" applied="" to="" many="" countries="" around="" the="" globe.="" additionally,="" author="" points="" out="" that in="" construction="" of="" chinese="" national="" spirit="" it="" is="" also="" important="" consider="" positive="" elements="" from="" different cultures="" in="" other="" nations. This book discusses the Chinese nation's spiritual home in a modern context. It analyzes various aspects of the problem, including background, theory, history, recent advances and solutions, from a global view. In discussing the development of Chinese national spirit, it also refers to western experiences of national culture and national spirit. To build the spiritual home, the traditional culture, values and faith need to be learned, analyzed and adapted to the modern context. Doing so helps to maintain the traditional characteristics while at the same time reinforcing new characteristics. This model can be applied to many countries around the globe. Additionally, the author points out that in the construction of Chinese national spirit it is also important to consider positive elements from different cultures in other nations.
Keywords: Social sciences.; Ethics.; Religion and culture.; elektronické knihy; electronic books